Double Death: Unique Presentation Of Accidental, Fatal Double Electrocution (Journal of Forensic Medicine & Toxicology, 2026)
Flow of electrical particles is responsible for electricity and when substantial electric current pass through the tissue, it leads to skin lesions, organ damage and death which is called electrocution.1 Most often, electrical fatalities are naturally accidental in nature.2 High voltage electrical injuries are relatively uncommon but, considerably contribute to occupa tional fatalities with the existence of hazardous exposure during their tasks at workplaces.3,4 This case reports a double electrocution accident due to contact with live wire lying unattended on the accident scene.
Keywords: Flow, electrical, particles, responsible, electricity